Geo park Area Of Tourism Products and Information Center in Kintamani, Bali - Yasa R, I Gede Danan Segara; Trimarianto, Ciptadi; Kastawan, I Wayan (Journal of A Sustainable Global South; Vol 5 No 1 (2021): February 2021DO - 10.24843/jsgs.2021.v05.i01.p06, 2021)
Tourism Information Center and Product Showcase is a place that functions to promote, inform and sell tourism prod-ucts in Kintamani.The function of this place is to inform the tourists who visit Batur Geopark so they can be more familiar with tourism products, which are divided into tourism products and goods products. Tourism products accommodated in this place are tourism object, tourism attraction, and service products, while for goods product accommodated are culinary products, handicrafts, and souvenirs. There are three important elements in designing: function, structure and aesthetic. From these elements, the aesthetic element is an element that distinguishes architecture from other design science. In order to achieve aesthetic element, there are 6 principles: (1) Unity, (2) Balance, (3) Proportion, (4) Scale, (5) Rhythm, and (6) Emphasis. In designing Information Center and Tourism Product Showcase of Batur Geopark in Kintamani the principles mentioned are applied to the building façade elements. Index Terms — information center and tourism product showcase, facade, aestheticsu